(untitled) (REMUNOM, 2025)
This article analyzes the (im)possibility of automatic exemption from child support payments for children who have reached the age of majority and the consequences and impacts of misinformation on the part of the payer. It is common sense to believe that the obligation to pay child support automatically ends when the child reaches the age of eighteen, but Brazilian law does not provide for this possibility and requires a court decision for the exemption to occur. This research aims to analyze the legal aspects involving the exemption from child support, through the analysis of the jurisprudence of the higher courts, as well as to demonstrate the importance of legal guidance and accessibility to information for those who pay child support regarding their obligation, seeking measures and strategies to ensure greater legal certainty and access to information for the parties involved.